Diagnostic Accuracy of Transient Elastography and Two-Dimensional Shear Wave Elastography for Staging Liver Fibrosis in Children or Adolescents: A Systematic Review and Meta-Analysis - Gong, Xiuru; Zhu, Tingting; Peng, Xiaolin; Xing, Dongwei; Zhang, Minguang (Current Medical Imaging, 2023)
Background: Few studies comprehensively compared the performance of transient elastography (TE) and two-dimensional shear wave elastography(2D-SWE) to diagnose the stage of liver fibrosis in children and adolescents. We assessed the diagnostic performance of these non-invasive imaging techniques from published studies. Methods: To evaluate the diagnostic performance of TE and 2D-SWE, we searched the PubMed, Embase, Web of Science, and Cochrane Library databases until November 13, 2021, for studies that diagnosed liver fibrosis in children and adolescents. Pooled sensitivity, specificity, positive and negative likelihood ratios, diagnostic odds ratios, and area under the receiver operating characteristic curve were estimated using the bivariate model. We also performed a subgroup analysis of various research characteristics. Results: Twenty-seven studies with 1956 patients were included in the analysis. The sensitivity and specificity of TE and 2D-SWE for detecting liver fibrosis in all stages were greater than 0.82. For the detection of significant fibrosis, advanced fibrosis and cirrhosis, the summary AUC was 0.90 (95% CI: 0.87-0.92), 0.95 (95% CI: 0.93-0.96) and 0.95 (95% CI: 0.93-0.97) for TE, and the summary AUC was 0.92 (95% CI: 0.89-0.94), 0.94 (95% CI: 0.92-0.96) and 0.96 (95% CI: 0.94-0.97) for 2D-SWE, respectively. Both imaging methods detected significant heterogeneity. mp;gt; Conclusion: TE and 2D-SWE can provide accurate non-invasive staging of liver fibrosis in children or adolescents and are a promising technology, particularly for advanced liver fibrosis and cirrhosis, with a high potential to replace liver biopsy.
Keywords: adolescents